From white-collar crime to red-collar crime - Brody, Richard G. (J Financ Crime, 2010)
PURPOSE: The purpose of this paper is to explore the issue of violence with respect to white-collar criminals. DESIGN/METHODOLOGY/APPROACH: The analysis is conceptual, focusing on the historical underpinnings of white-collar crime and reviewing the evolution of white-collar criminals. FINDINGS: Findings suggest that white-collar criminals do display violent tendencies and, contrary to popular belief, can become dangerous individuals. PRACTICAL IMPLICATIONS: The paper represents an extremely useful and practical source for fraud examiners and other white-collar crime investigators. Raising the mvareness of investigators dealing with white-collar criminals may prevent them from becoming victims of a violent act. ORIGINALITY/VALUE: The paper fulfills a need to highlight a dangerous trend with white-collar criminals in that they may be driven to violence against those involved in investigating their crimes.